Vitamin K and other markers of micronutrient status in morbidly obese patients before bariatric surgery. Issue 6 (11th December 2014) - Ewang‐Emukowhate, M.; Harrington, D. J.; Botha, A.; McGowan, B.; Wierzbicki, A. S.
Summary Background Micronutrient deficiencies occur in morbidly obese patients. The aim of this study was to assess vitamin deficiencies prior to bariatric surgery including vitamin K about which there is little data in this population. Methods A prospective assessment of 118 consecutive patients was performed. Clinical allied with haematological and biochemical variables were measured. Micronutrients measured included vitamins K1, PIVKA‐II (protein‐induced in vitamin K absence factor II), vitamin D, vitamin B12 (holotranscobalamin), iron, transferrin and folate. Results Patients were aged 49 ± 11 [mean (SD, standard deviation)] years, body mass index (BMI) 50 ± 8 kg/m2, 66% female and 78% Caucasian. Hypertension was present in 47% and type 2 diabetes in 32%. Vitamin D supplements had been prescribed in 8%. Micronutrient insufficiencies were found for vitamin K (40%), vitamin D (92%) and vitamin B12 (25%), and also iron (44%) and folate (18%). Normocalcaemic vitamin D insufficiency with secondary hyperparathyroidism was present in 18%. Iron and transferrin levels were associated with age, sex and estimated glomerular filtration rate. Vitamin K levels were associated with age, and inversely with BMI and diabetes mellitus; and PIVKA‐II with smoking, triglycerides and liver function markers. Vitamin D levels were associated with statin use and prescription of supplements and inversely with BMI. Vitamin B12 levels were associated with ethnicity and HbA1c. Conclusion Micronutrient status shows differing relationships with age, gender and BMI. Vitamin K insufficiency was present in 40% and not related to deficiencies in other vitamins or micronutrients. Vitamin D and vitamin K supplementation should be considered prebariatric surgery in patients with diabetes or severe insulin resistance.